Boosting the human antiviral response in conjunction with natural plant products - Srivastava, Rashmi; Dubey, Neeraj Kumar; Sharma, Megha; Kharkwal, Harsha; Bajpai, Rajesh; Srivastava, Rakesh (Frontiers in Natural Products, 2025)
The increasing prevalence of viral infections and the emergence of drug-resistant or mutant strains necessitate the exploration of novel antiviral strategies. Accumulating evidence suggests that natural plant products have significant potential to enhance the human antiviral response. Various plant natural products (PNPs) known for their antiviral properties have been evaluated for their ability to modulate immune responses and inhibit viral infections. Research has focused on understanding the mechanisms by which these PNPs interact with the human immune system and their potential to complement existing antiviral therapies. PNPs control compounds such as alkaloids, flavonoids, terpenoids, and polyphenols to promote antiviral cytokine synthesis, increase T-cell and macrophage activity, and activate antiviral genes. Studies have investigated the molecular interactions between PNPs, viruses, and host cells, exploring the potential of combining PNPs with conventional antiviral drugs to enhance efficacy. However, several challenges remain, including identifying, characterizing, and standardizing PNP extracts, optimizing dosages, improving bioavailability, assessing long-term safety, and navigating regulatory approval. The promising potential of PNPs is being explored to develop new, effective, and natural antiviral therapies. This review outlines a framework for an integrative approach to connect the full potential of PNPs in combating viral infections and improving human health. By combining natural plant products with conventional antiviral treatments, more effective and sustainable management of viral diseases can be achieved.